Educational Expertise, Advocacy, and Media Influence - Malin, Joel R.; Lubienski, Christopher (Education Policy Analysis Archives, 2015)
The efforts of many advocacy organizations to advance their preferred policies despite conflicting evidence of the effectiveness of these policies raise questions about factors that shape successful policy promotion. While many may like to think that expertise on an issue in question is an essential prerequisite for influence in public policy discussions, there is a traditional disconnect between research evidence and policymaking in many fields, including education. Moreover, the efforts of many policy advocates suggest that they see advantages in other factors besides research expertise in advancing their interpretation of evidence for use in policymaking processes. We hypothesize that some of the most influential education-focused organizations are advancing their agendas by engaging media and drawing on individuals who possess substantial media acumen, yet may not possess traditionally defined educational expertise. Thus, we hypothesize that media impact is loosely coupled with educational expertise. In fact, in analyzing various indicators of expertise and media penetration, we find a weak relationship between expertise and media impact, but find significantly elevated media penetration for individuals working at a sub-sample of organizations promoting what we term “incentivist” education reforms, in spite of their generally lower levels of expertise. We find these organizations are particularly effective in engaging new media forms by going directly to their audience. We consider the policy implications in the concluding discussion.